CHANGES IN PREHOSPITAL PHARMACOTHERAPY IN PATIENTS WITH ACUTE CORONARY SYNDROME IN 2005-2014 ACCORDING TO THE LIS REGISTER - S. Y. Martsevich; M. L. Ginzburg; N. P. Kutishenko; A. V. Zagrebelnyy; I. S. Balashov; L. G. Garkina (Рациональная фармакотерапия в кардиологии)
Aim. To study changes in prehospital pharmacotherapy with cardiovascular drugs in patients admitted to hospital with acute coronary syndrome (ACS) in 2005-2014.Material and methods. The data of the LIS register (Lyubertsy study of mortality in patients undergone acute myocardial infarction) were used. Patients that survived 4 days after admission were included in the analysis.Results. The positive changes in the prescription of antiplatelet agents (13.5% in 2005 and 27.4% in 2014), statins (1.7% and 16.3%, respectively) and angiotensin receptor blockers (0.6% and 8.8%, respectively) were found. The prescription rate of other cardiovascular drug classes did not change significantly.Conclusion. Registration of treatment prior to ACS can be an important tool for evaluation of quality of ACS and myocardial infarction drug prevention.